A novel tomato F‐box protein, SlEBF3, is involved in tuning ethylene signaling during plant development and climacteric fruit ripening. (19th June 2018) - Deng, Heng; Pirrello, Julien; Chen, Yao; Li, Nan; Zhu, Sihua; Chirinos, Ximena; Bouzayen, Mondher; Liu, Yongsheng; Liu, Mingchun
Summary: Ethylene is instrumental to climacteric fruit ripening and EIN3 BINDING F‐BOX (EBF) proteins have been assigned a central role in mediating ethylene responses by regulating EIN3/EIL degradation in Arabidopsis. However, the role and mode of action of tomato EBFs in ethylene‐dependent processes like fruit ripening remains unclear. Two novel EBF genes, SlEBF3 and SlEBF4, were identified in the tomato genome, and SlEBF3 displayed a ripening‐associated expression pattern suggesting its potential involvement in controlling ethylene response during fruit ripening. SlEBF3 downregulated tomato lines failed to show obvious ripening‐related phenotypes likely due to functional redundancy among SlEBF family members. By contrast, SlEBF3 overexpression lines exhibited pleiotropic ethylene‐related alterations, including inhibition of fruit ripening, attenuated triple‐response and delayed petal abscission. Yeast‐two‐hybrid system and bimolecular fluorescence complementation approaches indicated that SlEBF3 interacts with all known tomato SlEIL proteins and, consistently, total SlEIL protein levels were decreased in SlEBF3 overexpression fruits, supporting the idea that the reduced ethylene sensitivity and defects in fruit ripening are due to the SlEBF3‐mediated degradation of EIL proteins. Moreover, SlEBF3 expression is regulated by EIL1 via a feedback loop, which supposes its role in tuning ethylene signaling and responses. Overall, the study reveals the role of a novel EBF tomato gene in climacteric ripening, thus providing a new target for modulating fleshy fruit ripening. Significance Statement: This study uncovers a mechanism involving a novel F‐box protein, SlEBF3, which controls ethylene signaling, plant development and fruit ripening via regulating the levels of EIL proteins while its expression is regulated by EIL through a feedback loop in tomato.